The semantic guidance for mentioning and omitting the letters of meaning in verses with similar wording according to Badr al-Din Ibn Jama’ah (d. 733 AH) in his book (Unveiling the Meanings in the Similarities of the Mathani) - أحمد, دلير عبد الله; كريم, هيوا عبد الله (Sulaimani Journal for Humanities, 2019)
In Arabic language, mentioning and deletion of linguistic elements, creates different semantic senses. In Holy Quran, this subject appears more concisely and precisely, especially, in resembling verses of Quran. In this research, the semantic differences of these verses which, a great scientist (Badr Al-din bn Jamaha) has worked on it, have been illustrated as descriptive analysis. The research is comprised of an introduction, theoretical frame and three parts. In the first part, the semantic differences of mentioning and deletion of Prepositions, have been explained. The second part is concerned with, the semantic differences due to mentioning and deletion of the connectors. The third part is about the semantic differences of mentioning and deletion of the other Cohesive Devices have been demonstrated in a way linguistic elements have previously been mentioned in a verse of Quran while, deleted in others. Finally, the most important results have been displayed.